Analisis Keberlanjutan Sistem Pengelolaan Sampah Berbasis 3R (Studi Kasus MRF, TPST Kota Hijau, dan Bank Sampah Kota Hijau Balikpapan): Indonesia - Khairunisa, Khairunisa; Widyarsana, I Made Wahyu Widyarsana (UII, 2025)
As a buffer zone for the new National Capital (IKN), Balikpapan City is experiencing rapid population growth accompanied by increasing waste generation. In 2023, the city produced 528.87 tons of waste per day, an increase of 2.74% from the previous year. Projections indicate that the Manggar Landfill will reach full capacity by 2026, rendering it unable to accommodate additional waste. To address this issue, in 2017 the Balikpapan City Government, in collaboration with the Ministry of Environment and Forestry (KLHK) and JICA, implemented a 3R-based waste management program through the integration of Material Recovery Facilities (MRF), Integrated Waste Processing Facilities (TPST), and the Waste Bank Program. This study aims to analyze the factors influencing the sustainability of the waste management system at the MRF, TPST Kota Hijau, and Kota Hijau Waste Bank, and to formulate appropriate development strategies. The research applies Multidimensional Scaling (MDS) with the RAPFISH approach combined with SWOT analysis. The results show that the Kota Hijau Waste Bank has the highest sustainability status, supported by financial independence and strong community participation, and is classified as fairly sustainable. The MRF is also considered fairly sustainable but remains highly dependent on the municipal budget. Meanwhile, the TPST Kota Hijau records the lowest sustainability level due to operational-technical challenges and limited community involvement. Overall, the three infrastructures fall within the fairly sustainable category. To advance their status to sustainable or highly sustainable, several strategic measures are required, including the optimization of local policies and regulations, program synchronization across stakeholders, strengthening institutional and human resource capacities, diversifying funding sources, enhancing community engagement, and improving technical-operational performance.